Dynamics and status of physical development and physical fitness of students at the agricultural university - Nikolaev, E.A.; Ponomarev, V.V.; Kuzmina, S.N.; Smetanina, I.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the dynamics and state of physical development and physical fitness of students at an agricultural university (Krasnoyarsk) from the 1st to the 3rd year, to determine the problems and prospects of the processed results based on the factual material obtained, to develop appropriate methodological adjustments, and to recommend them for use in physical education for students at the university. Methods and structure of the study. The study was conducted between 2024 and 2025 at the educational base of Krasnoyarsk State Agrarian University. First- to third-year male students of the Krasnoyarsk Agrarian University took part in the experiment. The sample size was 180 people, 60 students in each year (1st to 3rd years). The groups of students were formed by random selection for analysis. The following research methods were selected to compile the factual material: analysis of scientific and educational literature, questionnaires, surveys, interviews, systematisation, abstraction, modelling, pedagogical observations, expert assessment, physical fitness testing, physical development measurements, mathematical statistics, etc. During the research period, more than 1,080 physical fitness tests and 900 physical development measurements were conducted. All this contributed to the collection of comprehensive factual material on students and the resolution of the scientific tasks set. Results and conclusions. The analysis of the dynamics and status of physical development and physical fitness showed the following statistical results: the physical development of students at the agricultural university (height, body weight, and hand dynamometry) decreased on average by (-9.1%) (p<0.05) from the first to the third year; the resting heart rate while sitting decreased by an average of -12.8% (p<0.05); physical fitness (pull-ups on a high bar, standing long jump, sit-ups per minute, 3000-metre run, 100-metre run, forward bend from a standing position) increased by an average of 2.0% (p<0.05). The final statistical results presented show that during their studies at the university, students (young men) of the agricultural university experienced a 9.1% decrease in physical development, a 12.8% improvement in heart rate (p<0.05) and a slight increase in physical fitness of 2.0%. All this, in general, indicates the need to make adjustments to the physical education programme for students at the agricultural university.